The bear (2020)
In 2018 the poet, the translator and the Argentinian Editor, Miguel Ángel Petrecca published a brief biography of the Enterrenian poet Carlos Mastronardi. The short story, fragmentary and aleatory, intervened in the most traditional motives and precedents of this literary genre: the archive configuration, the search for testimonies and the consecution of an independent style, away from the totalizing chronology. In this article, I propose a reading of Mastronardi through which I will expose the experimental characteristics of the text, fundamentally, the construction of the figures around the biographized: the witness and the biographer. The latter configured as the ironized figure of Juan José Saer: “the man who saw the man who saw the bear”.